Validação da Champion's Health Belief Model Scale para uso no Brasil - Moreira, Camila Brasil (2018)
Monitoring the adherence to mammography screening is an essential indicator for the early detection of breast cancer. The use of Champion's Health Belief Model Scale, a specific instrument for the identification and control of the mammographic examination adherence, has shown good results worldwide. This study aimed to validate the Champion's Health Belief Model Scale for the Brazilian Portuguese language. It is a methodological study developed in three stages: face validity with 40 women representatives of the target audience; content validity by 23 experts; and the construct validity with 206 women attended at a Primary Health Care Centre in Fortaleza-CE. The data were collected through the application of the translated and adapted scale and a sociodemographic and clinical data form related to the practice of early detection tests for breast cancer. The data were organized, tabulated and treated from Excel 2016 and SPSS 21.0, for the estimation and validation of the theoretical model the software AMOS 19.0 was used. For the face validity, the CVI analysis showed satisfactory indexes (100%), only one item had a CVI = 0.35. The content validity showed satisfactory validity indexes demonstrating that the items were comprehensible CVI (ranging from 0.91 to 1.0) and significant Kappa (p <0.001). For the construct validity, the confirmatory factorial analysis indicated considerable adjustments which led to the exploratory factorial analysis using the analysis of the main components with Varimax rotation that suggested the removal of 10 items from the scale. The reliability and internal consistency was verified by ICC (0.60-0.80; p <0.001) and Cronbach's alpha, which indicated the withdrawal of two more items. The final model resulted in a scale with 7 items divided into three domains with alpha ranging from 0.88 to 0.496. For the stability of the scale, Pearson's r and Spearman's ρ showed high stability (0.997 and 0.986). The final model of the factorial analysis underwent a validation process, confirming its consistency and reinforcing the robustness of the instrument. It was concluded that a reliable, valid instrument capable of assessing women's mammography adherence in the Brazilian context was obtained.